The Effect Of Giving Pineapple Juice And Honey On Reducing Menstrual Pain (Dysmenorrhea) In Adolescent Women At SMPN 1 Rangkasbitung Lebak Banten - Nineu Nineu; Titin Eka Sugiatini; Vina Oktiarina (Pusat Riset dan Inovasi Nasional, 2023)
Painful menstruation (Dysmenorrhea) is the most common cause of repeated absences from school. Several studies have shown that adolescents with dysmenorrhea experience a decrease in academic achievement, social and sports activities. Pain management pharmacologically, menstrual pain can be treated with analgesic therapy, which is the most commonly used method for pain relief (Potter and Perry, 2006). Meanwhile, Harahap's research (2020) found the effect of giving pineapple juice and honey on a decrease in menstrual pain in female adolescents. The purpose of this study was to determine the effect of giving pineapple juice and honey on reducing menstrual pain in young women at SMPN 1 Rangkasbitung Lebak Banten. The samples taken were 32 people with the criteria of being menstruating and dysmenorrhea, the data is not normally distributed then use the willcoxson test. Statistical test results using the SPSS 21 for Windows program obtained a Z value of -3.873 with a p value of 0.000, at alpha 0.05 it was known that p <alpha, it could be concluded that there was an effect of giving pineapple juice and honey on menstrual pain in young women.